Effects of active recovery after intensive training on performance and markers of fatigue in elite German weightlifters - Raeder, C.; Wiewlhove, T.; Schneider, C.; Döweling, A.; Ferrauti, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The aim of the present study was to investigate the effect of a repeated use of active recovery (ACT) compared with passive recovery (PAS) during a two-day heavy weightlifting training block with two training sessions per day on sport-specific performance and selected markers of fatigue. Methods: Eight competitive male (n=7) and female (n=1) German weightlifters from the Olympic national team participated in this study. In a crossover design, separated by a two-week wash-out period, the subjects performed either supervised ACT (submaximal rowing ergometer exercise; 1 Watt per kg body mass) or PAS (resting in a seated position) for 15 minutes after each training session. Sport-specific performance comprising maximal barbell velocity during the clean pull (CP) at 85% (CP85), 90% (CP90) and 95% (CP95) of the maximum load, as well as markers of fatigue including jump performance (countermovement jump, CMJ), skeletal muscle contractile properties (maximal displacement of the muscle belly, Dm; muscle contraction velocity, V90) using tensiomyography, muscle damage (serum creatine kinase activity, CK), muscle soreness (delayed onset muscle soreness, DOMS), and perceived overall stress and overall recovery levels (short recovery stress scale, SRSS) were measured one day before (Pre) and one day after (Post) completing the training programs. Results: There were neither significant recovery type x time interactions nor meaningful differences in prepost changes between ACT and PAS in all analyzed variables. However, the training block induced small decreases between Pre and Post over all relative intensities in CP (CP85, ACT: Effect size (ES)=-0.20, PAS: ES=-0.50; CP90, ACT: ES=-0.29, PAS: ES=-0.35; CP95, ACT: ES=-0.41, PAS: ES=-020; P>0.05). There were trivial pre-post changes in CMJ as well as in Dm and V90 in both interventions (ES<±0.20; P>0.05). Large to very large increases between Pre and Post could be found in CK (ACT: ES=2.11, PAS: ES=1.41; P=0.001) and DOMS (ACT: ES=1.65, PAS: ES=2.33; P=0.052) as well as moderate to large effects in perceived overall stress (ACT: ES=1.35, PAS: ES=1.01; P>0.05) and overall recovery levels (ACT: ES=-1.35, PAS: ES=-1.33; P>0.05). Discussion: The repeated use of individualized ACT seems not to promote recovery more effectively than PAS. However, ACT has also no detrimental effect on the recovery process compared with PAS. Therefore, the use of ACT should be considered at the individual level in the applied field.